Cheating detection in P2P online trading card games - Leal, Rodrigo R.; Simplicio Jr, Marcos A.; Santos, Mateus A. S.; Gomes, Marco A. L.; Goya, Walter A. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2013: Anais do XIII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2013.19544, 2013)
We present FairShuffle, a solution that allows players participating in Trading Card Game (TCG) match to detect cheating attempts right when they occur, and without the intervention of trusted third party (TTP). The protocol relies basically on commitment protocols built using hash functions, thus displaying a reduced computational cost. In addition, it displays many appealing characteristics, such as: support to multiple players; tolerance to players' dropouts during a match; resistance to collusion among any number of players. As such, FairShuffle is well-adapted for securing TCG games played in a peer-to-peer (P2P) environment.